Diet of fish fauna from Franco stream, Mato Grosso do Sul, Brazil - Brandão-Gonçalves, Lucas; Oliveira, Suelen Aparecida de; Lima-Junior, Sidnei Eduardo (Biota Neotropica, 2010)
Diet of fish fauna from Franco stream, Mato Grosso do Sul, Brazil. The aim of this study was to characterize the diet of the most abundant fish species in the Franco stream (Ivinhema, MS). Fish were captured monthly, from March 2006 to February 2007. To infer the diet of species that feed on macroscopic items, the stomach contents of each individual was removed, weighed (g) and subsequently analyzed under stereomicroscope. The data obtained for each species in each sampling unit were analyzed with the following methods: Frequency of Occurrence, Volumetric Analysis Index and Index of Importance. We collected 17 species of fish, the vast majority Characiformes, with ten species, two species of Siluriformes, two of Perciformes, two of Gymnotiformes and one of Synbranchiformes. The diet of two species of the genus Astyanax was based mainly on items of plant origin; Serrapinnus notomelas fed up of plant items, mainly from algae; Hemigrammus marginatus showed a mainly insectivorous feeding habits of alien origin, Corydoras aeneus and Eigenmannia trilineata fed up primarily of aquatic insects; sediment was the main food item of Hypostomus ancistroides, followed by algae and macrophytes; Crenicichla britiskii fed mainly on terrestrial insects.